Pengaruh E-Service Quality dan E-Trust Terhadap Keputusan Penggunaan Aplikasi BRImo Pada Masyarakat Di Kelurahan Tanjung Rejo Medan - Damayanti, Mei; Marbun, Patar; Salqaura, Siti Alhamra; Sabrina , Hesti (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the extent of the influence of e-service quality and e-trust on usage decisions. Data collection was conducted using both primary and secondary data. The population consists of all residents of Tanjung Rejo Subdistrict who have used BRI Mobile (BRImo). The sampling technique used was accidental sampling. The selected sample for this study amounted to 100 respondents. Data were collected through a questionnaire distributed online via Google Forms, which consisted of two parts. The first part contained questions related to the respondents’ characteristics, while the second part contained statements designed to understand respondents’ perceptions of e-service quality, e-trust, and usage decisions. This study employed validity and reliability testing using SPSS 25 for Windows (Statistical Product and Services Solutions). The results of this study indicate that e-service quality and e-trust have an influence on usage decisions. This shows that service quality and customer trust successfully influence the decision to use the service.